Stochastic wind-load model for building vibration estimation using large-eddy CFD simulation and random turbulence Flow generation Algorithms - Inaudi, Jose A. (2017)
Fil: Inaudi, Jose A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Departamento de Aeronáutica; Argentina.